Teampreneurship education as an answer to the challenges of the 21st century - Case study of Team Academy Debrecen - Árváné Ványi, Georgina; Katonáné Kovács, Judit; Gál, Tímea (Marketing & Menedzsment, 2019)
AIM OF THE PAPER Challenges o f the 21“ century require answers from higher education as well. In Europe, most o f the entrepreneurship programmes on the higher education institutions are less than ten years old. Whilst business studies may battle for academic legitimacy, it has a clear advantage when it comes to graduate employability. The aim o f this paper is to give answer to the following questions: why entrepreneurship education is important, what are the methods which are already used and what are the results o f them. METHODOLOGY USED The answers to the questions are based on literature reviews, a case study and in-depth interviews with alumni carried out at the University o f Debrecen, where since 2010 Team Academy Debrecen, a new education model from Finland is implemented. Tiimiakatemia education is an innovative model that develops team entrepreneurs. NOVELTY OF THE STUDY The experience o f the authors and the results o f the case study show, that with more than 20 years of experience, Tiiimiakatemia model is a good answer for the 'Teachability Dilemma', creativity and innovativeness (know-how and know-why components) are also teachable. Some important elements o f teachability are: learning by doing, passion, learning in teams and coaching. Entrepreneurship is leamt through experience. PROPOSALS OF THE STUDY In line with Haase and Lautenschlager (2011) suggestion - to change the role o f the entrepreneurship educator - in Tiimiakatemia team coaches support the work o f the students. Authors o f this paper also recommend the transformation o f entrepreneurship higher education first o f all with changing the role o f educators.